Analysis of Financial Feasibility and Marketing Management of Etawa Kaligesing Goat Farming Business: (Case Study of the Setia Farm Goat Breeder Group) - Vista Alifia Indriyani; Hesti Respatiningsih; Anes Arini (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This research aims to analyze the financial feasibility and marketing strategy of Etawa goat farming in Kaligesing District, which is recognized as one of the main centers for Etawa goat breeding in Indonesia. The case study was conducted at Setia Farm, a representative and active breeder in the region. The financial analysis employed several indicators, including Break-Even Point (BEP), Net Present Value (NPV), Internal Rate of Return (IRR), and Gross Benefit-Cost Ratio (Gross B/C). The findings show that the Gross B/C value reached 4.7, indicating a high return compared to investment cost. The NPV value was positive, and the IRR exceeded the prevailing loan interest rate, highlighting that the business generates significant profitability over time. Additionally, the BEP was achieved in a relatively short period, which signifies the business has strong potential for short-term capital recovery and low financial risk. From a marketing perspective, Setia Farm implements a combination of product excellence, adaptive pricing strategies, diverse distribution channels, and active promotional efforts. Their flagship products—mainly superior Etawa goats and processed dairy products—are positioned to meet market demand effectively. The farm also uses both direct marketing and digital platforms, such as social media and e-commerce, to expand its reach. Promotion is carried out through agricultural events, online campaigns, and collaboration with livestock communities. These strategies contribute to increasing brand awareness, building customer loyalty, and improving competitiveness. The integration of financial feasibility and strategic marketing supports the sustainability and growth of Etawa goat farming in Kaligesing. The results of this study can serve as a reference for livestock entrepreneurs, investors, and policymakers in developing similar agribusiness models that are profitable, resilient, and market-oriented.